Evaporation and crystallization of a droplet of desulfurization wastewater from a coal-fired power plant. (5th June 2017) - Liang, Zhengxing; Zhang, Li; Yang, Zhongqing; Qiang, Tang; Pu, Ge; Ran, Jingyu
Highlights: Evaporation and crystallization characteristics of the droplets of desulfurization wastewater. TGA and DSC methods were used to investigate the evaporation and crystallization processes. Evaporation and crystallization rates increase with the increase of temperature increasing rate. Increasing volume of the droplet increases the evaporation rate, but decreases the crystallization rate. Structure of the crystals changes significantly when the temperature increasing rate and the volume of the droplet change. Abstract: Relationship between evaporation and crystallization characteristics of a droplet of desulfurization wastewater from a coal-fired power plant and some operating conditions was studied experimentally using a thermogravimetric analyzer (TGA) with differential scanning calorimetry (DSC) function and a scanning electron microscope (SEM). The results shows that, between 15 °C/min and 45 °C/min, a higher temperature increasing rate leads to higher evaporation and crystallization rates. The increment in the evaporation rate, caused by the same increment of temperature increasing rate, is larger, when the temperature increasing rate is lower. In addition, the final temperatures, ranging from 90 °C to 150 °C, have little impact on the evaporation and crystallization rates of the 0.5 μL droplet. Ultimately, for the droplets, ranging from 0.2 μL to 2.5 μL, evaporation rate increases with increasing volumes of the droplets, but the crystallization rate decreases. From the SEM results, it can be observed that the quantity of cracks on the surface of the crystals also declines with the increase in volumes. Furthermore, the Stefan flow becomes a significant and unneglectable factor in order to decrease the evaporation rate at the end of the evaporation period.